Pengelolaan Keuangan Sesuai Standar Akuntansi Bagi Pelaku Usaha Home Industry “Kripik Cipuk” Di Desa Kadubeureum Kabupaten Serang - Santi Octaviani; Andari Andari (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2023)
At this time many see that the application of financial literacy knowledge in Cipuk MSMEs has not been applied optimally. However, with advances in technology, it has a method of applying business management knowledge so that these MSMEs can be more advanced. This business management science is financial literacy, which is to understand and apply various financial skills, such as managing personal savings, making budgeting, and investing. Not only that, MSMEs can add new flavor innovations due to the limited flavors in Cipuk preparations. The result of this service is that the Cipuk MSME partners understand more about financial literacy, understand more about making budgeting, financial bookkeeping and others, and add taste innovation, namely, so that MSME products are more varied and consumers don't feel bored with the taste of existing products.